Spectrophotometric Determination of Hexavalent Chromium after Complex Formation with EDTA Using H-Point Method - Lazo, Pranvera; Cullaj, Alqi; Lubonja, Filip (Asian Journal of Chemistry, 2010)
We have applied H-point spectrophotometric method to the analysis of water and industrial discharge samples for determination of microcontent of Cr6+ after its complex formation with EDTA, having the aim of increasing the sensitivity, accuracy, reproducibility and minimization of the method's bias. The concentration values of Cr6+ are reported for Durres region, near a chemical factory. The possibility for selective determination of Cr6+ in water and industrial discharges sample, simplicity and rapidity of this method make it suitable for screening large number of samples for environmental monitoring.